The Impact of Nutrition Education on Knowledge and Nutrition Label Comprehension in Adolescents - Suci, Puspita; Karyus, Aila; Puteri, Hidayatusy Syukrina (Genius Journal, 2026)
Introduction: Adolescence is a critical period of growth and development in which nutritional status and health behaviors play an important role in determining future health outcomes. Rapid lifestyle changes and increased consumption of packaged foods have contributed to rising nutritional problems among adolescents, including obesity and other non-communicable diseases. Understanding nutrition information on food labels is therefore essential to support healthy food choices and improve adolescents’ nutritional knowledge. Objective: Adolescents tend to consume packaged foods high in salt, sugar, and fat. One of the contributing factor is their low comprehension of the display of nutrition facts on the packaging and the habit of not reading them. Data from the Lampung Health Office show that the prevalence of obesity among school-aged children increased from 27% to 37% in 2021 and 2023. Reading nutrition facts is part of the Balanced Nutrition Guidelines. This study aims to analyze the effect of nutrition education using animated video media on knowledge and reading comprehension of nutrition facts on packaged foods among eight-grade adolescents at SMPN 2 Bukit Kemuning, Lampung Utara. Method: The study used a quantitative pre-experimental with a one-group pretest- posttest design. Nutrition education was delivered through animated video media, followed by measurement of knowledge and comprehension with a 14-days interval between the pretest and posttest. The study population consisted of 104 eight-grade students. Using a simple random sampling method, 84 samples were selected. However,the intervention was given to entire population to avoid sample loss, resulting in 85 samples collected. Data were analyzed using the Paired Sample T- Test. Result: The results showed a significant increase in the average score knowledge score from 64.05 to 89.07. And in reading comprehension from 59.34 to 85.53. Statitical tests showed a p-value <0.05 for both variables, indicating that nutrition education using animated video media had significant effect on improving adolescents knowledge and comprehension of reading nutrition facts.